Evidence of Small-Fiber Polyneuropathy in Unexplained, Juvenile-Onset, Widespread Pain Syndromes - Oaklander, Anne Louise (American Academy of Pediatrics, 2013)
OBJECTIVE: We tested the hypothesis that acquired small-fiber polyneuropathy (SFPN), previously uncharacterized in children, contributes to unexplained pediatric widespread pain syndromes. METHODS: Forty-one consecutive patients evaluated for unexplained widespread pain beginning before age 21 had medical records comprehensively analyzed regarding objective diagnostic testing for SFPN (neurodiagnostic skin biopsy, nerve biopsy, and autonomic function testing), plus histories, symptoms, signs, other tests, and treatments. Healthy, demographically matched volunteers provided normal controls for SFPN tests. RESULTS: Age at illness onset averaged 12.3 ± 5.7 years; 73% among this poly-ethnic sample were female (P = .001). Sixty-eight percent were chronically disabled, and 68% had hospitalizations. Objective testing diagnosed definite SFPN in 59%, probable SFPN in 17%, and possible SFPN in 22%. Only 1 of 41 had entirely normal SFPN test results. Ninety-eight percent of patients had other somatic complaints consistent with SFPN dysautonomia (90% cardiovascular, 82% gastrointestinal, and 34% urologic), 83% reported chronic fatigue, and 63% had chronic headache. Neurologic examinations identified reduced sensation in 68% and vasomotor abnormalities in 55%, including 23% with erythromelalgia. Exhaustive investigations for SFPN causality identified only history of autoimmune illnesses in 33% and serologic markers of disordered immunity in 89%. Treatment with corticosteroids and/or intravenous immune globulin objectively and subjectively benefited 80% of patients (12/15). CONCLUSIONS: More than half among a large series of patients with childhood-onset, unexplained chronic widespread pain met rigorous, multitest, diagnostic criteria for SFPN, which extends the age range of acquired SFPN into early childhood. Some cases appeared immune-mediated and improved with immunomodulatory therapies.